Continuous Gas-Phase Synthesis of Oxymethylene Dimethyl Ethers Using Supported Ionic Liquid Phase Catalysts - Aubermann, Manfred; Haumann, Marco; Wisser, Dorothea; Wasserscheid, Peter (ACS Sustainable Chemistry & Engineering, 2022)
Acidic supported ionic liquid phase catalysts were investigated for the synthesis of oxymethylene dimethyl ethers (OMEs). The application of OME1 and trioxane for the gas-phase synthesis of higher OMEs and in particular the generation of OMEn with n higher than 3 was successfully demonstrated. Raising the pressure led to an increase in the conversion of OME1 and to higher selectivity for higher molecular weight OMEs. Furthermore, a correlation between the ionic liquid's acidity and the catalytic activity was shown with higher acidity leading to higher conversion of trioxane and OME1. Moreover, successful long-term operation for more than 200 h time on stream has been demonstrated with good catalyst system stability.
CRIS-Team Scopus Importer:2022-06-17
Keywords: acid catalysis; continuous process; immobilization; oligomerization; supported ionic liquids

Improving the performance of supported ionic liquid phase (SILP) catalysts for the ultra-low-temperature water-gas shift reaction using metal salt additives - Wolf, Patrick; Aubermann, Manfred; Wolf, Moritz; Bauer, Tanja; Blaumeiser, Dominik; Stepic, Robert; Wick, Christian; Smith, David M.; Smith, Ana-Suncana; Wasserscheid, Peter; Libuda, Jörg; Haumann, Marco (Green Chemistry, 2019)
Supported ionic liquid phase (SILP) catalyst systems containing homogeneous Ru complexes dissolved in ionic liquids (ILs) catalyze the water-gas shift reaction (WGSR) at very low temperatures, i.e., between 120 and 160 °C. One limiting factor of the SILP WGS technology is the low solubility of CO in most ILs. To overcome this issue, we study the influence of different transition metal chloride additives on the activity of Ru-based WGS SILP catalysts. CuCl as the additive was found to enhance the activity by almost 30%. This increase in activity peaks at a CuCl addition of 4 M as a result of the interplay between the increasing CO uptake in the ionic liquid film as evidenced by means of CO sorption and thermogravimetry, and the increasing, unfavorable ionic liquid acidity at too high CuCl concentrations. The respective chlorocuprate species were identified by means of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) in combination with density functional theory (DFT) calculations. We attribute the enhanced catalytic performance to cuprate ions that act as CO shuttles within the ionic liquid film.
CRIS-Team Scopus Importer:2019-09-27

In-situ monitoring of homogeneously catalysed reactions using raman spectroscopy inside hollow-core photonic crystal fibres - Schorn, Florian; Aubermann, Manfred; Zeltner, Richard; Wasserscheid, Peter; Haumann, Marco; Joly, Nicolas (Optics InfoBase Conference Papers, 2020)
We monitor the reaction of an acid with an alcohol inside a hollow-core photonic crystal fibre using Raman spectroscopy. The method uses tiny amount of chemicals and allows precise measurement of the activation energy.
CRIS-Team Scopus Importer:2020-11-13